Communication practices in a multicultural library - L. Kh. Satarova (Библиосфера, 2013)
The article considers the multicultural library as an establishment where the representatives of different ethnic groups invariably meet and there is a unique opportunity for system formation, mutual understanding, supportive psychological situation and possibility for intercultural education.